Cultural Heritage and Mobile Robotics Technologies - D'Ell Erba, Ramiro; Conte, Giuseppe; Scaradozzi, David; Bandera-Rubio, Juan Pedro (My University, 2016)
This paper reviews current research works at the authors’ Institutions to illustrate how mobile robotics and related technologies can be used to enhance economical fruition, control, protection and social impact of the cultural heritage. Robots allow experiencing on-line, from remote locations, tours at museums, archaeological areas and monuments. These solutions avoid travelling costs, increase beyond actual limits the number of simultaneous visitors, and prevent possible damages that can arise by over-exploitation of fragile environments. The same tools can be used for exploration and monitoring of cultural artifacts located in difficult to reach or dangerous areas. Examples are provided by the use of underwater robots in the exploration of deeply submerged archaeological areas. Besides, technologies commonly employed in robotics can be used to help exploring, monitoring and preserving cultural artifacts. Examples are provided by the development of procedures for data acquisition and mapping and by object recognition and monitoring algorithms.
Patrimonio Cultural y Tecnologías Robóticas Móviles
Keywords: Robótica; Cultural Heritage; Robotics